ANALISIS PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KEMBALI YANG DIMEDIASI OLEH KEPUASAN PELANGGAN (Suatu Studi Pada Scarlett Whitening Mitra Tokopedia) - Sony Dharmawan; Syafrizal Chan (Journal of Fundamental Management (JFM), 2022)
Competition between companies is getting tougher to present quality beauty products so that they can be an option for consumers. This study aims to examine and analyze the effect of product quality, promotion and brand image on repurchase decisions mediated by customer satisfaction (study on Tokopedia partner Scarlett Whitening). The data of this research are data taken from the company's secondary data and primary data obtained from the processing of questionnaire data filled out by Scarlett Whitening consumers who have made purchases more than once. The number of samples used as many as 135 respondents and the analysis technique used in this study is to use Partial Least Square (PLS) analysis. The findings of previous researchers indicate that product quality, promotion and brand image have a positive and significant influence on repurchase decisions and customer satisfaction. In addition, customer satisfaction also has a positive effect on repurchase decisions.